The Role of Religious Extracurricular Activities in Improving Students' Insight and Morals at Smpn 41 Bandung - Rifqi Fathan Saepudin Muzakki; Mokh Iman Firmansyah; Syahidin Syahidin (AL-FIKRA, 2024)
AbstractThe practice of Islamic religious education in public schools that is less than optimal with limited time allocation makes it difficult to provide adequate religious knowledge, attitudes and skills to students. Therefore, alternative strategies are needed to meet the needs of religious education in public schools. This research specifically aims to describe and examine, (1) Identification of strategies and methods used in extracurricular activities, (2) The role of religious extracurricular activities in broadening students' horizons and moral formation, (3) Exploration of the role of guilt in moral education through religious extracurricular activities at school, (4) Analysis of the impact of social interaction in religious extracurricular activities on the understanding of moral codes and students' adaptation motivation. Religious extracurriculars at this school have become an initiative to bring students closer to Islam with a more practical and interactional method. This study used a qualitative approach with observation, interview, and document analysis methods to collect data. The implication of this study is that schools can consider and develop more religious extracurricular programs as part of efforts to improve students' religious and moral understanding. In addition, it contributes to improving the reputation and achievements of educational institutions. This research can also be a reference for educational policy makers and related parties in designing religious extracurricular programs. Key words: Religious Extracurricular; Moral Education; Student Insight. Praktik pendidikan agama Islam di sekolah umum yang kurang maksimal dengan alokasi waktu yang terbatas membuat sulit dalam memberikan pengetahuan, sikap, dan keterampilan agama yang memadai kepada peserta didik. Oleh karena itu, diperlukan strategi alternatif untuk memenuhi kebutuhan pendidikan agama di sekolah umum. Penelitian ini secara khusus bertujuan untuk mendeskripsikan dan mengkaji, (1) Identifikasi strategi dan metode yang digunakan dalam ekstrakurikuler, (2) Peran ekstrakurikuler keagamaan dalam memperluas wawasan dan pembentukan moral siswa, (3) Eksplorasi peran rasa bersalah dalam pendidikan moral melalui ekstrakurikuler keagamaan di sekolah, (4) Analisis dampak interaksi sosial dalam ekstrakurikuler keagamaan terhadap pemahaman kode moral dan motivasi adaptasi siswa. Ekstrakurikuler keagamaan di sekolah ini telah menjadi inisiatif untuk lebih mendekatkan siswa kepada Islam dengan metode yang lebih praktis dan berinteraksi. Penelitian ini menggunakan pendekatan kualitatif dengan metode observasi, wawancara, dan analisis dokumen untuk mengumpulkan data. Implikasi dari penelitian ini adalah sekolah dapat mempertimbangkan dan mengembangkan lebih banyak program ekstrakurikuler keagamaan sebagai bagian dari upaya meningkatkan pemahaman agama dan moral siswa. Selain itu, berkontribusi pada peningkatan reputasi dan prestasi institusi pendidikan. Penelitian ini juga dapat menjadi referensi bagi pengambil kebijakan pendidikan dan pihak terkait dalam merancang program pendukung yang lebih efektif untuk pendidikan agama di Indonesia.Kata kunci: Ekstrakurikuler Keagamaan, Pendidikan Moral, Wawasan Siswa